Human rights in Sub Saharan Africa: Understanding the influence of militarization, governance and democracy - Chimere Okechukwu Iheonu; Shedrach A. Agbutun; Chinedum J. Chiemela (African Governance and Development Institute (AGDI), 2021)
This study provides empirical evidence on the impact of militarization, governance, and democracy on human rights in sub-Saharan Africa (SSA) for the period 2002 to 2018. The study employed the instrumental variable Fixed Effects model to account for simultaneity/reverse causality, and unobservable heterogeneity as well as the instrumental variable quantile regression with Fixed Effects to account for existing levels of human rights in SSA. Based on the Fixed Effects results, it is revealed that militarization significantly increases human rights violation in the region, while governance and democracy significantly improve human rights. Results from the quantile regression show that (1) the negative impact of militarization on human rights is observable across all quantiles, (2) the positive impact of the control of corruption on human rights is more pronounced in countries where the existing level of human rights is high, while political stability and rule of law exerts stronger impact on human rights in countries where the existing level of human rights is low, (3) the positive impact of democracy on human rights is stronger in countries where the existing level of human rights is high. Policy recommendations based on these findings are discussed.
Keywords: C21; C23; K38; 330; Human Rights; Militarization; Governance; Democracy; Sub-Saharan Africa